Question
Sun September 22, 2013 By: Naveen S Nair
 

a cot? + b cosec ? =p and b cot ? + a cosec ? =q then what is p2-q2

Expert Reply
Sun September 22, 2013

p2= (a cot ? + b cosec ?)2 = acot? + b2 cosec2? + 2ab cot ? cosec ?

q2= (b cot ? + a cosec ?)2 = b2cot2? + acosec2? + 2ab cot ? cosec ?

p2- q= acot? + b2 cosec2? + 2ab cot ? cosec ? - (b2cot2? + acosec2? + 2ab cot ? cosec ?)

= acot? - acosec2? + b2 cosec2? - b2cot2?

= a2  (cot ? - cosec2 ? ) + b ( cosec2? - cot2?)

= a 2 (-1) + b (1)

b - a 2

Home Work Help